Caroline Moreira Eufrausino’s Anne Enright. Feminine Aesthetics: Writing, Mothering, Spiraling - Barros del Río, María Amor (ABEI Journal, 2021)
Eufrausino, Caroline. Anne Enright. Feminine Aesthetics: Writing, Mothering, Spiraling. Peter Lang, 2021.